EFFECTIVENESS OF WORK MOTIVATION AND EMPLOYEE ABILITIES TO THE DISTRICT LOCAL GOVERNMENT ORGANIZATION GIVE IT GORONTALUS - Syamsu Qamar Badu; Novianty Djafri (International Journal of Artificial Intelligence for Digital Marketing, 2024)
A government organization has a predetermined purpose. Success in achieving these goals is not only from government operational funds, facilities and infrastructure, and technology, but depends on human resources. Therefore, this study aims to see the influence of work motivation and employee ability on the effectiveness of local government organizations, with the hypothesis that "there is a positive influence of work motivation and employee ability on organizational effectiveness". The research method used is a causal survey method with multiple regression analysis techniques. This research is a quantitative research so that the data obtained, processed and analyzed statistically (parametric). Based on the data analysis that has been carried out, this study produces the following conclusions: (i) work motivation and ability together have a significant effect on organizational effectiveness; (ii) self-motivation (partial) has a significant effect on organizational effectiveness; (iii) the ability to itself (partially) has a significant effect on the effectiveness of the organization.